2010
DOI: 10.1242/jcs.069641
|View full text |Cite
|
Sign up to set email alerts
|

Physiological levels of TNFα stimulation induce stochastic dynamics of NF-κB responses in single living cells

Abstract: SummaryNuclear factor kappa B (NF-B) signalling is activated by cellular stress and inflammation and regulates cytokine expression. We applied single-cell imaging to investigate dynamic responses to different doses of tumour necrosis factor alpha (TNF). Lower doses activated fewer cells and those responding showed an increasingly variable delay in the initial NF-B nuclear translocation and associated IB degradation. Robust 100 minute nuclear:cytoplasmic NF-B oscillations were observed over a wide range o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
110
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(128 citation statements)
references
References 39 publications
14
110
1
Order By: Relevance
“…The amount of IL-6 mRNA was increased by IFN-g slightly, although the increase was not statistically significant. Previous studies suggested that the physiological levels of TNF-a are much lower than those that we use in in vitro experiments (10 ng/ml) (39,40). Thus, we stimulated cpdm MEFs with 0.1 ng/ml TNF-a and found that IFN-g pretreatment did not increase the amount of TNF-a and VCAM-1 mRNA, although it significantly induced IL-6 mRNA (Fig.…”
Section: Ifn-g Suppresses Apoptosis But Does Not Effectively Augment mentioning
confidence: 62%
“…The amount of IL-6 mRNA was increased by IFN-g slightly, although the increase was not statistically significant. Previous studies suggested that the physiological levels of TNF-a are much lower than those that we use in in vitro experiments (10 ng/ml) (39,40). Thus, we stimulated cpdm MEFs with 0.1 ng/ml TNF-a and found that IFN-g pretreatment did not increase the amount of TNF-a and VCAM-1 mRNA, although it significantly induced IL-6 mRNA (Fig.…”
Section: Ifn-g Suppresses Apoptosis But Does Not Effectively Augment mentioning
confidence: 62%
“…3T3 cell lysates were used as reference controls. Experiments were performed at this dose, as the physiological (15 pg/ml) and pathogenic (5 ng/ml) levels of TNF-a did not elicit measurable changes in many in vitro experimental studies 32 Figure 1c) were unaffected at the physiological and pathogenic doses of TNF-a. Cell viability based on trypan blue dye exclusion further revealed high mortality in granulocytes treated with 50 ng/ml TNF-a at 4 and 24 h. In contrast, mortality was low in granulocytes treated with doses less than 50 ng/ml at all time points (Supplementary Table I).…”
Section: Resultsmentioning
confidence: 99%
“…Both Tay et al and Turner et al have shown that not all cells respond to low concentrations of TNFα, and that this is probably due to a heterogonous digital process. IKK (the inhibitor of IκB) needs multiple phosphorylation steps to become activated, which could lead to a digital cellular response profile [43,44].…”
Section: Modelingmentioning
confidence: 99%